Bison - Grunbaum, Mara (2019)
Did you know that bison are the largest mammals in North America-or that they've lived in Yellowstone since prehistoric times? Learn fascinating factstitle offers a complete picture of the animal- from birth to adulthood- and describes its place in our world, including how humans impact it and its environment. like these-and more-all in the pages of this book! This
Includes bibliographical references (page 46) and index.
8-11
Keywords: Bison -- Juvenile literature